Analisis Solusi Kemacetan pada Simpang Sebidang Kereta Api Jalan Urip Sumoharjo - Hutapea, Raditya Eros Witantra; Herianto, Dwi; Siregar, Amril Ma'ruf (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
The high frequency of the Babaranjang train track causes congestion problems on the Urip Sumoharjo road which is caused by road closures when the train passes. The impact of the closure caused long queues of vehicles to block Padjajaran and Kimaja roads. In this study, it discusses the causes of congestion in the vehicle movement that is not smooth, especially on the Simpang Urip Sumoharjo road. Then compare the road capacity and the degree of saturation of the Urip Sumoharjo road under normal conditions and the conditions when the Babaranjang train passes, and analyze the structural concept to overcome congestion at the Urip Sumoharjo crossing.Analyze the comparison between Flyover and Underpass using the Scoring Zero One method. The results of the analysis show that to overcome congestion on Jalan Urip Sumoharjo it is more effective to build an underpass with a score of 60% while the flyover building gets a score of 40%. With the cross-normal degree of saturation, the result is 0.711. As for the results of saturation after the train passed the result was 1.56. And the calculation results show that the existence of an underpass can reduce congestion on Jalan Urip Sumoharjo by 45.58%.Keywords: Railroad latch, Degree of Saturation, Scoring Zero One method